2008
DOI: 10.1055/s-2007-965808
|View full text |Cite
|
Sign up to set email alerts
|

Side Effects of Anabolic Androgenic Steroids Abuse

Abstract: Long-term side effects of high doses of anabolic androgenic steroids self-administration were evaluated in this study. Twenty male bodybuilders, voluntarily starting steroid self-administration, were followed every 6 months over 2 years. Physical examination, haematological, metabolic and endocrine variables, semen analysis, hepatic and prostate ultrasound and echocardiographic evaluations were performed. LH values (baseline 3.43 +/- 1.75) were suppressed at 18 (1.98 +/- 1.99) (p = 0.026) and 24 (2.43 +/- 2.17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 40 publications
2
65
0
4
Order By: Relevance
“…Anabolic androgenic steroids induce these effects by dispersing the neuroendocrine function in females [7,18]. In the normal female body, a little testosterone is produced, and artificial materials increase the level of anabolic androgens in the blood which will affect the hypothalamic-pituitary-gonadal axis and change the normal functions of the axis.…”
Section: V(ref): = a T A: = A(p)mentioning
confidence: 99%
See 1 more Smart Citation
“…Anabolic androgenic steroids induce these effects by dispersing the neuroendocrine function in females [7,18]. In the normal female body, a little testosterone is produced, and artificial materials increase the level of anabolic androgens in the blood which will affect the hypothalamic-pituitary-gonadal axis and change the normal functions of the axis.…”
Section: V(ref): = a T A: = A(p)mentioning
confidence: 99%
“…It has been reported that negative feedback is suppressed by high levels of circulating anabolic androgen, thereby reducing the dis- www.fhc.viamedica.pl charge of gonadotropin. As a result, an increase in the circulating androgens will inhibit the production and release of LH and FSH, leading to a decline in the serum levels of LH, FSH, estrogens, and progesterone [7,18]. This may result in the inhibition of follicle formation and ovulation.…”
Section: V(ref): = a T A: = A(p)mentioning
confidence: 99%
“…2 The endocrine effects of AAS abuse are well established and commonly include testicular atrophy, decreased fertility, and gynecomastia. 3 Additional adverse effects associated with AASs include changes in blood lipid levels (increase in LDL and decrease in HDL), 4 various forms of hepatotoxicity, 5 and neuropsychiatric disturbances. 6,7 We present the first series of patients who developed FSGS after long-term use of AASs.…”
Section: Introductionmentioning
confidence: 99%
“…Particularmente, a redução dos níveis de FSH pode levar a diminuição da contagem, da mobilidade e alteração da morfologia dos espermatozoides (17) . Em relação ao LH, essa redução leva a alteração da sinalização para a síntese e posterior liberação de testosterona; possivelmente, essa é uma explicação para os baixos níveis de testosterona encontrados em usuários de esteroides anabolizantes, dependendo da classe de sustâncias utilizadas.…”
Section: Discussionunclassified